Evolution of ASEAN-Japan Relations - Sudo, Sueo (Book collections on Project MUSE., 2005)
Charts the progress of ASEAN-Japan relations from their difficult wartime legacy to postwar moves at diplomatic and economic rapprochement through successive governments.